Charles Schulz, great cartoonist - Mascola, Marilyn, 1949-; Lazzarino, Luciano (Vero Beach, Fla. : Rourke Enterprises, 1989)
A brief biography of the famous cartoonist who created the comic strip, "Peanuts." Presents suggestions for the reader in pursuing a goal.
3.5
K-3
Keywords: Schulz, Charles M., -- 1922-2000 -- Juvenile literature; Schulz, Charles M., -- 1922-2000.; Schulz, Charles M., -- 1922-2000.; Cartoonists -- United States -- Biography -- Juvenile literature; Cartoonists; Cartoonists -- Biography; Cartoonists -- Biography